Chitosan rare earth composite adsorption material and preparation method and application thereof
The chitosan rare earth composite adsorption material formed by glutaraldehyde cross-linking and rare earth material coordination reaction solves the problems of low adsorption amount and poor stability when removing methyl blue, and achieves efficient removal of methyl blue and maintain stability in acidic media.
Patent Information
- Application Number
- CN202310210729.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The adsorption amount of existing adsorbents is low when removing methyl blue in water, and has poor stability in acidic media, making it difficult to effectively deal with environmental pollution.
Glutaraldehyde crosslinked spherical chitosan material is coordinated and reacted with rare earth materials to form chitosan rare earth composite adsorption material, enhancing the stability and adsorption ability of the material.
The adsorption amount is increased to 740.7 mg/g, which significantly improves the removal ability of methyl blue, and maintains stability under different pH environments. It is suitable for removing anionic dye pollutants in the environment.
Smart Images

Figure CN116159541B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a chitosan rare earth composite adsorption material and a preparation method and application thereof. Background Art
[0002] Dyes are widely used in many fields such as plastics, food, paper and cosmetics industries. When the amount of dyes discharged into the environment exceeds the natural environment's repair capacity, it will have a significant impact on the environment and human health. 37 H 27 N 3 Na 2 O 9 S 3 , molecular weight: 799.07 g mol -1 ) is a commonly used water-soluble dye used as a colorant and disinfectant in the dyeing process. When methylene blue is discharged into the water environment, it will not only affect the appearance of the water body and cause visual pollution, but also reduce the transparency of the water body, affect the survival of aquatic plants and animals, and destroy the ecological balance of the water body. Therefore, it is of great significance to remove methylene blue from the water body.
[0003] The treatment methods for dyes mainly include adsorption, membrane separation, biological treatment, etc. Among them, the adsorption method is simple, convenient, flexible, and more suitable for practical applications. However, the main problem of the adsorption method is the lack of adsorbents with high adsorption capacity.
[0004] CN115282932A discloses the preparation and application of a lignin-modified adsorbent, which uses sodium lignin sulfonate as a structure-directing agent and polyanion dopant to provide more active sites for aniline monomers. Polyaniline grows along the long chain of lignin, so that the composite material has a significant specific surface area, providing sufficient space for the adsorption of dyes. However, its adsorption capacity is still relatively low, and the saturated adsorption capacity for malachite green is only 108.79 mg / g.
[0005] CN113908802A discloses a copper-based composite for adsorbing organic anionic dyes. Although the preparation method is simple, the optimal adsorption amount of Congo red is only 400 mg / g.
[0006] Chitosan is the most abundant biopolymer extracted from the waste of the seafood processing industry. It has great advantages in adsorption due to its low cost, simple polymerization and functionalization process, and good stability. Chitosan contains amino and hydroxyl groups. Due to chelation and electrostatic attraction, chitosan can not only be used as an adsorbent to remove pollutants such as heavy metals and dyes, but can also be easily modified to prepare functional chitosan substrate materials. However, due to the good crystal expansion of chitosan raw materials, low porosity, low hydrophilicity, small specific surface area, poor stability in acidic media, low adsorption capacity in aqueous media, and the adsorption capacity of pollutants is often reduced after cross-linking with a cross-linking agent.
[0007] Therefore, it is very meaningful to develop adsorption materials with strong adsorption capacity and simple preparation process. Summary of the invention
[0008] In view of the deficiencies of the prior art, the object of the present invention is to provide a chitosan rare earth composite adsorption material and a preparation method and application thereof.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a chitosan rare earth composite adsorption material, wherein the chitosan rare earth composite adsorption material comprises a chitosan material cross-linked into a spherical shape by using glutaraldehyde and a rare earth material loaded on the chitosan.
[0011] The chitosan rare earth composite adsorption material of the present invention is a spherical chitosan material, wherein the chitosan monomer is cross-linked into a spherical shape by glutaraldehyde, and the rare earth material reacts with the amino group and the hydroxyl group in the chitosan to be loaded on the chitosan to form the chitosan rare earth composite material of the present invention. The rare earth material reacts with the chitosan to protect the amino group and the hydroxyl group in the chitosan, and enhance the stability of the composite material, especially the pH stability. The high pH stability can effectively avoid the problem of poor stability of the chitosan under the acidic medium; in addition, the chitosan composite adsorption material prepared by the present invention has a large specific surface area and a strong adsorption capacity, and the adsorption amount of methyl blue can reach 740.7mg / g. Therefore, the chitosan rare earth composite adsorption material prepared by the present invention has a large adsorption amount and strong stability, and has a good application prospect in removing anionic dye pollutants such as methyl blue in the environment.
[0012] Preferably, the molecular weight of the chitosan is in the range of 50,000 to 350,000;
[0013] The specific value of 50,000-350,000 can be 50,000, 100,000, 150,000, 200,000, 250,000, 300,000 or 350,000, etc.;
[0014] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0015] Preferably, the deacetylation degree of the chitosan is 80-95%.
[0016] The specific value of 80-95% may be 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94% or 95%, etc.;
[0017] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0018] Preferably, the rare earth material comprises rare earth salts;
[0019] Preferably, the cations in the rare earth salts include any one of cerium ions, europium ions, lanthanum ions, yttrium ions, terbium ions, neodymium ions, gadolinium ions, praseodymium ions, samarium ions, erbium ions or dysprosium ions, or a combination of at least two of them; the combination of at least two includes a combination of cerium ions and europium ions, a combination of lanthanum ions and yttrium ions, or a combination of neodymium ions and gadolinium ions, and any other combinations may be selected and will not be described in detail here.
[0020] Preferably, the cations in the rare earth salts include cerium ions or lanthanum ions;
[0021] Preferably, the cation in the rare earth salt is a cerium ion;
[0022] When the cations in the rare earth salts of the present invention include cerium ions or lanthanum ions, the chitosan rare earth composite material has a strong adsorption capacity. When the cations in the rare earth salts specifically select cerium ions, the adsorption effect of the chitosan composite adsorption material is better.
[0023] Preferably, the anions in the rare earth salts include any one of nitrate ions, chloride ions or sulfate ions, or a combination of at least two of them; the combination of at least two includes a combination of nitrate ions and chloride ions, a combination of nitrate ions and sulfate ions, or a combination of sulfate ions and chloride ions, and any other combinations can be selected and will not be described in detail here.
[0024] Preferably, the anions in the rare earth salts are nitrate ions.
[0025] When the anions in the rare earth salts involved in the present invention are nitrate ions, the composite material has a stronger adsorption effect.
[0026] Preferably, the mass ratio of the rare earth material to the chitosan material is 1:(10-100); more preferably, the mass ratio of the rare earth material to the chitosan material is 1:(12-38).
[0027] The specific value of 10-100 can be 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, etc.;
[0028] The specific value of 12-38 can be 12, 15, 20, 25, 30, 35 or 38, etc.;
[0029] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0030] When the mass ratio of the rare earth material to the chitosan material is specifically selected to be 1:(10-100) in the present invention, the chitosan rare earth composite material has good adsorption performance. When the mass ratio of the rare earth material to the chitosan material is 1:(12-38), the adsorption performance of the chitosan rare earth composite material is even better.
[0031] In a second aspect, the present invention provides a method for preparing the chitosan rare earth composite adsorption material as described in the first aspect, the preparation method comprising the following steps:
[0032] (1) mixing a rare earth material solution with chitosan to prepare a mixed solution;
[0033] (2) Add the mixed solution dropwise into the oil phase and stir at 40-60°C for 0.5-3h;
[0034] (3) dripping the glutaraldehyde solution into the solution obtained in step (2), stirring, centrifuging, washing, and vacuum freeze-drying to obtain the chitosan rare earth composite adsorption material.
[0035] The chitosan rare earth composite material of the present invention is prepared by mixing rare earth material and chitosan, dripping the mixture into oil phase, dripping glutaraldehyde solution into the mixture, stirring, centrifuging, washing, and vacuum freeze drying. The preparation method of the present invention is simple in process and suitable for industrial scale-up.
[0036] The specific value of 40-60°C can be 40°C, 43°C, 46°C, 49°C, 52°C, 55°C, 58°C or 60°C, etc.;
[0037] The specific value of 0.5-3h can be 0.5h, 1h, 1.5h, 2h, 2.5h or 3h, etc.;
[0038] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0039] Preferably, in step (1), the rare earth material is immersed in an acetic acid aqueous solution before mixing;
[0040] Preferably, the soaking temperature is 20-30°C and the soaking time is 8-16h;
[0041] The specific value of 20-30°C can be 20°C, 22°C, 24°C, 26°C, 28°C or 30°C, etc.;
[0042] The specific value of 8-16h can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h, etc.;
[0043] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0044] Preferably, the concentration of the acetic acid aqueous solution is 1 wt %.
[0045] Preferably, the mixing in step (1) further comprises stirring;
[0046] Preferably, the stirring speed is 500-700 rpm.
[0047] The specific value of 500-700rpm can be selected from 500rpm, 550rpm, 600rpm, 650rpm or 700rpm, etc.;
[0048] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0049] Preferably, the oil phase in step (2) comprises any one of liquid paraffin, Span-20, Span-40, Span-60, Span-80 or Tween-80, or a combination of at least two of them; the combination of at least two comprises a combination of liquid paraffin and Span-20, a combination of Span-20 and Span-40, or a combination of Span-60 and Span-80, etc. Any other combinations may be selected and will not be described in detail here.
[0050] Preferably, the oil phase in step (2) comprises liquid paraffin and / or Span-80.
[0051] Preferably, the oil phase in step (2) comprises a combination of liquid paraffin and Span-80.
[0052] When the oil phase of the present invention includes liquid paraffin and / or Span-80, the adsorption capacity of the prepared chitosan rare earth composite material is higher. When the oil phase includes a combination of liquid paraffin and Span-80, the adsorption capacity of the composite material is further improved.
[0053] Preferably, the mass ratio of the liquid paraffin to Span-80 is (12-48):1.
[0054] The specific value in (12-48) can be 12, 15, 25, 30, 35, 40, 45 or 48, etc.;
[0055] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0056] Preferably, the stirring speed in step (2) is 500-700 rpm.
[0057] The specific value of 500-700rpm can be selected from 500rpm, 550rpm, 600rpm, 650rpm or 700rpm, etc.;
[0058] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0059] Preferably, the concentration of the glutaraldehyde solution in step (3) is 10-30 wt%.
[0060] The specific value of the 10-30wt% may be 10wt%, 15wt%, 20wt%, 25wt% or 30wt%, etc.;
[0061] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0062] Preferably, the stirring speed in step (3) is 500-700 rpm, and the stirring time is 0.5-3 h.
[0063] The specific value of 500-700rpm can be selected from 500rpm, 550rpm, 600rpm, 650rpm or 700rpm, etc.;
[0064] The specific value of 0.5-3h can be 0.5h, 1h, 1.5h, 2h, 2.5h or 3h, etc.;
[0065] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0066] Preferably, the centrifugation time in step (3) is 2-10 min.
[0067] The specific value of 2-10 min can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc.
[0068] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0069] Preferably, the centrifugal speed in step (3) is 100-8000 rpm.
[0070] The specific value of 10-8000rpm can be selected from 100rpm, 1000rpm, 2000rpm, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm or 8000rpm, etc.;
[0071] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0072] Preferably, the washing liquid in step (3) is water and / or anhydrous ethanol;
[0073] Preferably, the vacuum freeze-drying time in step (3) is 20-30 hours.
[0074] The specific value of 20-30h can be selected from 20h, 22h, 24h, 26h, 28h or 30h, etc.;
[0075] Other specific point values within the above numerical ranges can be selected and will not be described in detail here.
[0076] In a third aspect, the present invention provides the use of the chitosan rare earth composite adsorption material as described in the first aspect or the preparation method as described in the second aspect in waste liquid adsorption treatment.
[0077] Compared with the prior art, the present invention has the following beneficial effects:
[0078] 1. The chitosan rare earth composite adsorption material of the present invention is a spherical chitosan material, wherein the chitosan monomer is cross-linked into a spherical shape by glutaraldehyde, and the rare earth material reacts with the amino group and the hydroxyl group in the chitosan to be loaded on the chitosan to form the chitosan rare earth composite material of the present invention. The rare earth material reacts with the chitosan to protect the amino group and the hydroxyl group in the chitosan, and enhance the stability of the composite material, especially the pH stability. The high pH stability can effectively avoid the problem of poor stability of the chitosan under the acidic medium; in addition, the chitosan composite adsorption material prepared by the present invention has a large specific surface area and a strong adsorption capacity, and the adsorption amount of methyl blue in the waste liquid can reach 740.7mg / g. Therefore, the chitosan rare earth composite adsorption material prepared by the present invention has a large adsorption amount and strong stability, and has a good application prospect in removing anionic dye pollutants such as methyl blue in the environment.
[0079] 2. When preparing the chitosan rare earth composite material of the present invention, it is only necessary to mix the rare earth material with chitosan, drip the mixture into the oil phase, drip glutaraldehyde solution into the mixture, stir, centrifuge, wash, and vacuum freeze-dry to obtain the composite material. The preparation method of the present invention is simple in process and suitable for industrial amplification. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 This is the SEM characterization result of the material obtained in Example 1.
[0081] Figure 2 This is a graph showing the variation of the amount of methyl blue adsorption over time for the material prepared in Example 1 in Test Example 3. DETAILED DESCRIPTION
[0082] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0083] The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention has no particular restrictions. The experimental methods without specifying specific conditions in the embodiments are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0084] Unless otherwise specified, all technical terms and scientific terms used in this specification have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. However, in case of any conflict, the present specification including the definitions shall prevail.
[0085] In the following content, liquid paraffin is a product of analytical grade purchased from Sinopharm Chemical Reagent Co., Ltd.; Span-80 is a product of analytical grade purchased from Sinopharm Chemical Reagent Co., Ltd.
[0086] Example 1
[0087] This embodiment provides a chitosan rare earth composite adsorption material, and the preparation method of the chitosan rare earth composite adsorption material is as follows:
[0088] (1) 1 part of cerium nitrate was placed in a 1 wt % acetic acid aqueous solution and soaked at 25° C. for 10 h; 25 parts of chitosan (80,000 molecular weight, 90% deacetylation degree) was added, the chitosan concentration was 1 wt %, and the mixture was stirred at 600 rpm until the chitosan was completely dissolved;
[0089] (2) 20 mL of the solution prepared in step (1) was added dropwise into 100 mL of an oil phase (the oil phase was prepared by mixing 19 parts of liquid paraffin and 1 part of Span-80), and stirred at 60° C. and 600 rpm for 1.5 h;
[0090] (3) 4 mL of 25 wt% glutaraldehyde solution was dripped into the solution obtained in step (3), stirred at 600 rpm for 1 h, centrifuged at 8000 rpm for 5 min, and the precipitate was washed twice with anhydrous ethanol, washed twice with ultrapure water, and vacuum freeze-dried for 30 h to obtain the chitosan rare earth composite adsorbent material (the SEM result of the obtained material is shown in FIG. Figure 1 shown).
[0091] Example 2
[0092] This embodiment provides a chitosan rare earth composite adsorption material, and the preparation method of the chitosan rare earth composite adsorption material is as follows:
[0093] (1) 1 part of cerium nitrate was placed in a 1 wt % acetic acid aqueous solution and soaked at 20° C. for 16 h, 25 parts of chitosan (molecular weight 90,000, 95% deacetylation degree) was added, the chitosan concentration was 1 wt %, and the mixture was stirred at 500 rpm until the chitosan was completely dissolved;
[0094] (2) 20 mL of the solution prepared in step (1) was added dropwise to the oil phase (the oil phase was prepared by mixing 19 parts of liquid paraffin and 1 part of Span-80), and stirred at 60° C. and 600 rpm for 3 h;
[0095] (3) 4 mL of 30 wt% glutaraldehyde solution was dropped into the solution obtained in step (3), stirred at 700 rpm for 0.5 h, centrifuged at 8000 rpm for 5 min, and the precipitate was washed twice with anhydrous ethanol and twice with ultrapure water, and vacuum freeze-dried for 30 h to obtain the chitosan rare earth composite adsorption material.
[0096] Example 3
[0097] This embodiment provides a chitosan rare earth composite adsorption material, and the preparation method of the chitosan rare earth composite adsorption material is as follows:
[0098] (1) 1 part of cerium nitrate was placed in a 1 wt % acetic acid aqueous solution at 30° C. and soaked for 8 h, 25 parts of chitosan (molecular weight of 85,000, degree of deacetylation of 90%) were added, the chitosan concentration was 1 wt %, and the mixture was stirred at 700 rpm until the chitosan was completely dissolved;
[0099] (2) 20 mL of the solution prepared in step (1) was dropped into the oil phase (the oil phase was prepared by mixing 19 parts of liquid paraffin and 1 part of Span-80), and stirred at 40° C. and 600 rpm for 0.5 h;
[0100] (3) 4 mL of 10 wt% glutaraldehyde solution was dropped into the solution obtained in step (3), stirred at 500 rpm for 3 h, centrifuged at 8000 rpm for 5 min, and the precipitate was washed twice with anhydrous ethanol and twice with ultrapure water, and vacuum freeze-dried for 30 h to obtain the chitosan rare earth composite adsorption material.
[0101] Example 4
[0102] This embodiment provides a chitosan rare earth composite adsorption material. The preparation method thereof is different from that of embodiment 1 only in that the preparation raw material does not contain cerium nitrate, and cerium nitrate is replaced by lanthanum nitrate in equal moles. The rest of the operations are the same as those of embodiment 1.
[0103] Example 5
[0104] This embodiment provides a chitosan rare earth composite adsorption material. The preparation method thereof is different from that of embodiment 1 only in that the preparation raw material does not contain cerium nitrate, and cerium nitrate is replaced by terbium nitrate in equal moles. The rest of the operations are the same as those of embodiment 1.
[0105] Example 6
[0106] This embodiment provides a chitosan rare earth composite adsorption material. The preparation method thereof is different from that of embodiment 1 only in that the preparation raw material does not contain cerium nitrate, and cerium nitrate is replaced by cerium sulfate in equal moles. The rest of the operations are the same as those of embodiment 1.
[0107] Example 7
[0108] This embodiment provides a chitosan rare earth composite adsorption material. The preparation method thereof is different from that of embodiment 1 only in that the preparation raw material does not contain cerium nitrate, and cerium nitrate is replaced by cerium chloride in equal moles. The rest of the operations are the same as those of embodiment 1.
[0109] Example 8
[0110] This embodiment provides a chitosan rare earth composite adsorption material, and its preparation method is different from that of Example 1 only in that 1 part of cerium nitrate and 25 parts of chitosan (the mass ratio of rare earth material to chitosan material is 1:25) in the preparation raw materials are replaced by 2.36 parts of cerium nitrate and 23.6 parts of chitosan (the mass ratio of rare earth material to chitosan material is 1:10), and the rest are the same as Example 1.
[0111] Example 9
[0112] This embodiment provides a chitosan rare earth composite adsorption material, and its preparation method is different from that of Example 1 only in that 1 part of cerium nitrate and 25 parts of chitosan (the mass ratio of rare earth material to chitosan material is 1:25) in the preparation raw materials are replaced with 0.63 parts of cerium nitrate and 25.37 parts of chitosan (the mass ratio of rare earth material to chitosan material is 1:40), and the rest are the same as Example 1.
[0113] Example 10
[0114] This embodiment provides a chitosan rare earth composite adsorption material. The preparation method thereof is different from that of Embodiment 1 only in that 19 parts of liquid paraffin and 1 part of Span-80 are replaced by 10 parts of liquid paraffin and 1 part of Span-80, and the rest is the same as that of Embodiment 1.
[0115] Embodiment 11
[0116] This embodiment provides a chitosan rare earth composite adsorption material. The preparation method thereof is different from that of Embodiment 1 only in that 19 parts of liquid paraffin and 1 part of Span-80 are replaced by 50 parts of liquid paraffin and 1 part of Span-80, and the rest is the same as that of Embodiment 1.
[0117] Comparative Example 1
[0118] This comparative example provides a commercial chitosan material, which is a food-grade product purchased from Qingdao Bozhihuili Biotechnology Co., Ltd.
[0119] Comparative Example 2
[0120] This comparative example provides an adsorbent material, the adsorbent material is Fe 3 O 4 -CS / EDTA, which was prepared by referring to the Fe in the Materials and Methods section of the journal (Chen, B. et al., A magnetically recyclable chitosan composite adsorbent functionalized with EDTA for simultaneous capture of anionic dye and heavy metals in complex wastewater. Chemical Engineering Journal 2019, 356, 69-80. DOI: 10.1016 / j.cej.2018.08.222.) 3 O 4 -CS / EDTA preparation method.
[0121] Comparative Example 3
[0122] This comparative example provides an adsorbent material, the adsorbent material is Na-doped gC 3 N 4 The preparation method of the methyl blue was based on the Na-doped gC in the Materials and Methods section of the journal (Fronczak, M et al., Extraordinary adsorption of methyl blue onto sodium-doped graphitic carbon nitride. The Journal of Physical Chemistry C 2017, 121(29), 15756-15766.). 3 N 4 Preparation method is prepared.
[0123] Comparative Example 4
[0124] This comparative example provides an adsorbent material, which is GO / CS sponge, and its preparation is prepared by referring to the GO / CS sponge preparation method in the materials and methods section of the journal literature (Qi et al., Graphene oxide / chitosan sponge as a novel filtering material for the removal of dye from water. Journal of colloid and interface science 2018, 517, 18-27.).
[0125] Test Example 1
[0126] This test example evaluates the adsorption capacity of the materials obtained in each embodiment or comparative example. The specific evaluation method is:
[0127] A 300 mg / L methyl blue solution was prepared, and the pH was adjusted to 6. 15 mg of the material prepared in each embodiment or comparative example was placed in 25 mL of methyl blue solution, and adsorbed at 30° C. and 150 rpm until the methyl blue concentration no longer changed. The adsorption amount was calculated. The adsorption amount calculation formula was: q=(C0-C1)*V / m. The results are shown in Table 1.
[0128] Wherein C0 is the initial concentration of methyl blue, C1 is the equilibrium concentration of methyl blue, V is the volume of methyl blue solution; m is the mass of chitosan rare earth composite material; q is the adsorption amount of methyl blue by chitosan rare earth composite material.
[0129] Table 1
[0130] Group Adsorption capacity (mg / g) Example 1 741 Example 2 710 Example 3 704 Example 4 700 Example 5 692 Example 6 684 Example 7 700 Example 8 652 Example 9 610 Example 10 643 Embodiment 11 660 Comparative Example 1 231 Comparative Example 2 460 Comparative Example 3 360 Comparative Example 4 275
[0131] It can be seen from the data in Table 1 that, compared with Example 1, the rare earth materials in Examples 4 and 5 do not contain cerium ions but contain lanthanum ions or terbium ions, and their adsorption amounts are lower than that in Example 1, indicating that the composite material prepared by combining the rare earth element cerium with chitosan has a stronger adsorption capacity than lanthanum or terbium.
[0132] Compared with Example 1, in Examples 6 and 7, sulfate ions and chloride ions are selected as anions in the rare earth elements, respectively, and their adsorption amounts are lower than that in Example 1, indicating that nitrate ions are more suitable than other anions for preparing the chitosan rare earth composite material.
[0133] Compared with Example 1, the mass ratio of rare earth material to chitosan material in Example 8 and Example 9 is not in the range of 1:(12-38), and the adsorption amount is lower than that in Example 1, indicating that when the mass ratio of the two materials is in the range of 1:(12-38), the adsorption function of the prepared composite material is stronger.
[0134] Compared with Example 1, the mass ratio of Span-80 to liquid paraffin in Example 10 and Example 11 is not in the preferred range of 1:(12-48), and the adsorption amount is lower than that in Example 1, indicating that when the mass ratio of the two materials is in the preferred range of 1:(12-48), the adsorption effect is better.
[0135] Comparative Example 1 uses commercial chitosan, and its adsorption amount is lower than that of Example 1, indicating that the present invention uses glutaraldehyde to cross-link chitosan into a sphere, and loads rare earth materials on chitosan. The prepared chitosan rare earth composite material can significantly improve the adsorption of anionic dyes, and the adsorption amount is more than three times that of the chitosan product.
[0136] Comparative Examples 2-4 respectively use common adsorbents, and their adsorption amounts are also lower than those of Example 1, indicating that the chitosan rare earth composite material prepared by the present invention has good adsorption effect and great potential in the adsorption of anionic dyes such as methyl blue.
[0137] Test Example 2
[0138] This test example evaluates the pH stability of the material obtained in Example 1 or Comparative Example 1. The specific evaluation method is:
[0139] A 300 mg / L methyl blue solution was prepared, and the pH of the methyl blue solution was adjusted to 3, 4, 5, 6, 7, 8, 9, and 10 using sodium hydroxide or hydrochloric acid, and 15 mg of the material prepared in the embodiment or the comparative example was placed in 25 mL of methyl blue solution with different pH values, and adsorbed at 30° C. and 150 rpm until the methyl blue concentration no longer changed, and the adsorption amount was calculated. The adsorption amount calculation formula was: q=(C0-C1)*V / m. The results are shown in Table 2.
[0140] Where C0 is the initial concentration of methyl blue, C1 is the equilibrium concentration of methyl blue, V is the volume of the methyl blue solution; m is the mass of the material; and q is the amount of methyl blue adsorbed by the material.
[0141] Table 2
[0142]
[0143]
[0144] It can be seen from the data in Table 2 that the chitosan rare earth composite material prepared by the present invention can maintain an adsorption amount of not less than 690 mg / g in the pH range of 3-10, and the adsorption amount gradually increases with the decrease of pH. This may be due to the strong electrostatic interaction between the composite material and methyl blue when the pH is low.
[0145] The difference between the highest adsorption amount and the lowest adsorption amount of the present invention at different pH values is 78 mg / g, accounting for 10.6% of the average adsorption amount (732.5 mg / g) under different pH environments, while the difference between the highest adsorption amount and the lowest adsorption amount of the commercial chitosan in the comparative example at different pH values is 82 mg / g, accounting for 42.7% of the average adsorption amount (192.25 mg / g) under different pH environments. Therefore, the chitosan rare earth composite material prepared by the present invention has stronger pH stability than the commercial chitosan.
[0146] Test Example 3
[0147] This test example evaluates the change of the adsorption amount of the material prepared in Example 1 over time. The specific evaluation method is:
[0148] Prepare a 300 mg / L methyl blue solution, adjust the pH of the methyl blue solution to 3, take 15 mg of the material prepared in Example 1 and place it in 25 mL of methyl blue solution, perform adsorption at 30°C and 150 rpm, and record the adsorption amount at 10 min, 30 min, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h and 16 h after the adsorption begins. The adsorption amount is calculated using the formula: q = (C0-C1) * V / m, where C0 is the initial concentration of methyl blue, C1 is the equilibrium concentration of methyl blue, V is the volume of the methyl blue solution; m is the mass of the chitosan rare earth material; and q is the adsorption amount of methyl blue by the chitosan rare earth material. The results are as follows: Figure 2 shown.
[0149] Depend on Figure 2 As can be seen from the results, the chitosan rare earth composite material prepared by the present invention is in a rapid adsorption process at 60 minutes, and the adsorption amount at this moment can reach half of the saturated adsorption amount. In addition, the adsorption of the composite material reaches equilibrium at 6 hours. It shows that the composite material of the present invention has fast adsorption, good adsorption effect, and high adsorption stability, and has broad application prospects when applied to waste liquid with harsh adsorption environment.
[0150] The applicant declares that the present invention illustrates the preparation process of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0151] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0152] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. Application of a chitosan rare earth composite adsorption material in methylene blue adsorption treatment, characterized in that: The chitosan rare earth composite adsorption material comprises a chitosan material cross-linked into a spherical shape by using glutaraldehyde and a rare earth material loaded on the chitosan; The rare earth materials include rare earth salts; The cations in the rare earth salts are cerium ions or lanthanum ions; The anions in the rare earth salts are nitrate ions or chloride ions.
2. The use according to claim 1, characterized in that The molecular weight of the chitosan is 50,000-350,000.
3. The use according to claim 1, characterized in that The deacetylation degree of the chitosan is 80-95%.
4. The use according to claim 1, characterized in that The cations in the rare earth salts are cerium ions.
5. The use according to claim 1, characterized in that The anions in the rare earth salts are nitrate ions.
6. The use according to claim 1, characterized in that The mass ratio of the rare earth material to the chitosan material is 1:(10-100).
7. The use according to claim 6, characterized in that The mass ratio of the rare earth material to the chitosan material is 1:(12-38).
8. The use according to any one of claims 1 to 7, characterized in that The preparation method of the chitosan rare earth composite adsorption material comprises the following steps: (1) mixing a rare earth material solution with chitosan to prepare a mixed solution; (2) Add the mixed solution dropwise into the oil phase and stir at 40-60°C for 0.5-3h; (3) dripping the glutaraldehyde solution into the solution obtained in step (2), stirring, centrifuging, washing, and vacuum freeze-drying to obtain the chitosan rare earth composite adsorption material.
9. The use according to claim 8, characterized in that In step (1), the rare earth material is immersed in an acetic acid aqueous solution before mixing.
10. The use according to claim 9, characterized in that The soaking temperature is 20-30° C. and the soaking time is 8-16 hours.
11. The use according to claim 8, characterized in that The step (1) further comprises a stirring operation after the mixing.
12. The use according to claim 11, characterized in that The stirring speed in step (1) is 500-700 rpm.
13. The use according to claim 8, characterized in that The oil phase in step (2) comprises any one of liquid paraffin, Span-20, Span-40, Span-60, Span-80 or Tween-80, or a combination of at least two thereof.
14. The use according to claim 13, characterized in that The oil phase in step (2) comprises liquid paraffin and / or Span-80.
15. The use according to claim 14, characterized in that The oil phase in step (2) comprises a combination of liquid paraffin and Span-80.
16. The use according to claim 15, characterized in that The mass ratio of the liquid paraffin to Span-80 is (12-48):
1.
17. The use according to claim 8, characterized in that The stirring speed in step (2) is 500-700 rpm.
18. The use according to claim 8, characterized in that The concentration of the glutaraldehyde solution in step (3) is 10-30wt%.
19. The use according to claim 8, characterized in that The stirring speed in step (3) is 500-700 rpm, and the stirring time is 0.5-3 h.
20. The use according to claim 8, characterized in that The centrifugation time in step (3) is 2-10 min.
21. The use according to claim 8, characterized in that The centrifugal speed in step (3) is 100-8000 rpm.
22. The use according to claim 8, characterized in that The washing liquid in step (3) is water and / or anhydrous ethanol.
23. The use according to claim 8, characterized in that The vacuum freeze-drying time in step (3) is 20-30 hours.
Citation Information
Patent Citations
Copper-based compound for organic anionic dye adsorption
CN113908802A
Adsorption method of lignin-based adsorbent for dye wastewater
CN115282932A
Chitosan-rare earth composite membrane and preparation method and application thereof
CN108114703A
Magnetic microsphere as well as preparation method and application thereof
CN113058563A